High-energy Modification Hydrates of Copper(II) Sulphate: heats of solution and infrared spectrum - Badri, M.; Crouse, Karen Anne (1982)
High-energy modification of lower hydrates of copper(II) sulphate have been prepared and their heats of solution measured. The values obtained are higher than previously found for the salt. A new mechanism of dehydration has been proposed and supported by ir study of deuterated sample.